Performance of Beams Made of Low-cost Self-compacting Concrete in an Aggressive Environment - M. A. Safan (Acta Polytechnica, 2011)
Self-Compacting Concrete mixes (SCC) incorporating silica fume, fly ash and dolomite powder were used in casting two groups of beams. The beams in one group were stored in an open environment, while those in the other group were subjected to salt attack and successive wet/drying cycles. The beams were stored for about one year under a sustained load. The structural performance of the stored beams was evaluated by testing the specimens under four-point loading until failure. The results indicated that the low-cost SCC mixes showed comparable structural behavior with respect to the corresponding control mixes in a normal environment. Different SCC mixes in a corrosive environment yielded a different structural performance, depending on the composition of the fillers.